Returns to citizenship?: evidence from Germany's recent immigration reforms - Gathmann, Christina; Keller, Nicolas (SOEP papers on multidisciplinary panel data research, 2014)
Immigrants in many countries have lower employment rates and earnings than natives. We study whether the option to naturalize improves immigrant assimilation. The empirical analysis relies on two major immigration reforms in Germany, a country with a weak record of immigrant integration. Using discontinuities in the reforms' eligibility rules, we find few returns of citizenship for men, but substantial returns for women. Returns are also larger for more recent immigrants, but essentially zero for traditional guest workers. For immigrant women, access to citizenship accounts for 70% of the assimilation rate, i.e. the wage return of an additional year in Germany.
Keywords: Graue Literatur